Cr-Doped FeC2O4 Microrods Formed Directly on AISI 420 Stainless Steel to Enhance Electrochemical NO3- Reduction to N2 at Circumneutral pH - Rahman, Evandi; Lee, Jiho; Lim, Seung Ji; Son, Aseom; Han, Jiyun; Cho, Kangwoo; Hong, Seok Won (American Chemical Society, 2023)
We synthesized low-cost cathodes for use in the electrochemical NO3- reduction reaction (NO3RR) via the simple reconstruction of AISI 420 stainless steel (SS). Thermochemical treatment of the SS in oxalic acid generated iron oxalate (FeC2O4) microrods (BL-SS), with further anodization affording Cr-doped Fe2O3 (R-SS) or FeC2O4 (G-SS). G-SS displayed supreme N-2 selectivity during galvanostatic electrolysis at circumneutral pH. Electroanalysis and descriptor/scavenger analysis indicated that Fe sites were the primary active sites of NO3- adsorption, with C2O42- as the H-binding sites. The C2O42- ligands and Cr dopants altered the electronic structures of the Fe sites. A parametric study of the current density, pH, [NO3-](0), and [Cl-](0) indicated an Eley-Rideal N-2 generation mechanism, with NO2- as an intermediate. Cl- elevated the N-2 selectivity but reduced the NO3RR efficiency. To demonstrate the practical applicability of G-SS with a proposed regeneration strategy, its durability was examined in synthetic and real wastewater matrices. Compared with that in synthetic wastewater, G-SS displayed more stable performance in real wastewater owing to the natural buffering capacity at the cathode, which reduced the corrosion rate. Cr-doped FeC2O4 is viable for use in the low-cost, efficient electrochemical treatment of wastewater containing NO3-.